A review on the theories of adoption telemedicine in Middle Ease: toward building Iraqi telemedicine - Abd Ghani, Mohd Khanapi; Jaber, Mustafa Musa (WSEAS Transactions On Proof, 2022)
Telemedicine is the use of modern telecommunications and information technologies for the provision of clinical care to individuals at a distance, and transmission of information to provide that care. Recent advances in information technology and biomedicine increased significantly the technical feasibility, clinical feasibility and affordability enabled collaborative of telemedicine and medical service delivery. Health organizations around the world are becoming more interested in the acquisition and implementation the telemedicine technology to improve or expand existing services and patient care. The ultimate success of telemedicine in an organization requires the adoption of adequate care both technological and managerial issues. This study examined the adoption theories, the key management problem facing many health care organizations which interested in or currently evaluating telemedicine . this research models targeted the technology adoption and empirically evaluated in a study of the investigation involving more public health agencies and criticize the theories. Several research and management implications that emerged from the study results are discussed.